Politics and popular opinion in East Germany : 1945 - 68 - Allinson, Mark (Manchester Univ. Press [u.a.], 2000)
"This groundbreaking work examines East Germany's postwar development from the defeat of Nazism to the stabilisation of a new socialist state by 1968. Using a wide range of many previously unexamined contemporary documents, the book investigates how ordinary East Germans experienced this extraordinary political and social upheaval, and how central policy decisions were translated into the reality of everyday life in the provinces. Allinson shows how some East Germans, at their own behest, worked alongside the Soviet occupiers to construct the new socialist order, while others merely tolerated or opposed their masters. Particular emphasis is placed on the attempt to co-opt East Germany's Christian churches and young people to 'real existing socialism'."--BOOK JACKET.